Answer:
See below for answers (in bold) and explanations
Step-by-step explanation:
Part A: (h+t)(x) = h(x) + t(x) = (2x-5) + (6x+4) = 2x - 5 + 6x + 4 = 8x - 1
Part B: (h*t)(x) = h(x) * t(x) = (2x-5) * (6x+4) = (2x)(6x) + (2x)(4) + (-5)(6x) + (-5)(4) = 12x² + 8x - 30x - 20 = 12x² - 22x - 20
Part C: h(t(x)) = h(6x + 4) = 2(6x + 4) - 5 = 12x + 8 - 5 = 12x + 3
Answer:
1. A. AC=3IN
2. D AND C
Step-by-step explanation:
Answer: The percent of change is 25%
Step-by-step explanation:
$525 - $393.75 = $131.25
131.25 (amount of change)/525 ( original amount) x 100
= 25%
Answer:
x=−18
Step-by-step explanation:
Let's solve your equation step-by-step.
x
3
+4=−2
Step 1: Simplify both sides of the equation.
1
3
x+4=−2
Step 2: Subtract 4 from both sides.
1
3
x+4−4=−2−4
1
3
x=−6
Step 3: Multiply both sides by 3.
3*(
1
3
x)=(3)*(−6)
x=−18